Self-monitoring of blood glucose levels in patients with type 2 diabetes mellitus - Konstantin V. Ovsyannikov; Evgeny A. Praskurnichiy (LLC "MEDIAFORMAT", 2024)
Self-monitoring of blood glucose has been considered to be a cornerstone of adequate diabetes management for decades. The structured self-monitoring leads to better compensation of carbohydrate metabolism disorders, decreased risk of hypoglycemia, and quality of life improvement in patients with DM. The technologies, as well as the glucose meter convenience and accuracy have improved considerably since the moment these were introduced several decades ago. Modern glucose meters are small and easy to use; these require small amounts of capillary blood and provide measurement results within seconds. Furthermore, glucose meters are more and more often equipped with such features, as connectivity with other devices and/or electronic diaries and instruments for diabetes management. Despite the fact that the measurement accuracy can be close to or equal to the quality level ensured by laboratory biochemical analyzers, some glucose meters continue to fall short of the internationally accepted accuracy standards, such as ISO-15197, the standard of the International Organization for Standardization. Numerous reports from the number of countries, such as Russia, China, India, and Brazil, that are based on the routine practice data suggest that in addition to the problems with the glucose meter accuracy, there are other obstacles to overcome to optimize the use of blood glucose monitoring systems. Nevertheless, the adequate use of blood glucose self-monitoring data is very important for treatment of patients with type 2 diabetes mellitus.